2020
DOI: 10.3389/fendo.2020.00533
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Proteomic and MicroRNA Analysis: Insights Into Mechanisms of Eyestalk Ablation-Induced Ovarian Maturation in the Swimming Crab Portunus trituberculatus

Abstract: Eyestalk ablation is the most common method to induce ovarian maturation in decapod crustacean aquaculture, but it jeopardizes broodstock survival and larvae production. It is important to understand the molecular basis underlying the maturation triggered by ablation and thereby develop an alternative measure for maturation manipulation. In this study, we investigate alterations of ovarian proteome and miRNA profile after ablation in a commercially important marine crab Portunus trituberculatus. Quantitative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 71 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…β-actin was used as the internal control. Specific primers were designed based on gene sequences from our previous transcriptome data or previous studies (Zhang et al, 2009;Cui et al, 2010;Meng et al, 2014Meng et al, , 2015Meng et al, , 2020Ren et al, 2016; Table 1). The reactions were performed with the following program: 95 • C for 30 s; 94 • C for 5 s, and 60 • C for 15 s (35-40 cycles).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…β-actin was used as the internal control. Specific primers were designed based on gene sequences from our previous transcriptome data or previous studies (Zhang et al, 2009;Cui et al, 2010;Meng et al, 2014Meng et al, , 2015Meng et al, , 2020Ren et al, 2016; Table 1). The reactions were performed with the following program: 95 • C for 30 s; 94 • C for 5 s, and 60 • C for 15 s (35-40 cycles).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…miRNAs are also essential for ovulation and oocyte maturation in invertebrates (Kadener et al, 2009). In decapods, several sexrelated miRNAs have been identified in S. paramamosain (Jia et al, 2018;Waiho et al, 2019a;Zhou et al, 2019Zhou et al, , 2020, Portunus trituberculatus (Meng et al, 2018(Meng et al, , 2020, E. sinensis (Song et al, 2014;He et al, 2015), M. rosenbergii (Liu X. et al, 2019;Qiao et al, 2019) M. nipponense (Sb et al, 2015;Jin et al, 2017), P. monodon (Zhao et al, 2018), and Fenneropenaeus merguiensis (Saetan and Chotigeat, 2019). The roles of sex-related miRNAs in decapods are summarized in Table 3.…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…In addition, the expression level of miR-87 and miR-7 was significantly increased and they were predicted to target cyclin-dependent kinase 2 (Cdk2)7 and cell division cycle4 (Cdc4), which are important for regulation of the G1-to-S-phase transition during the cell cycle (Schnackenberg et al, 2007). Meng et al (2020) showed that MF synthesis and FAMeT expression are directly regulated by miR-4171 and miR-263a. Also, miR-317, miR-2b, and miR-466f-3p repress the expression of calcium signal transduction (CaM).…”
Section: Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…The swimming crab, Portunus trituberculatus (Crustacea: Decapoda: Brachyura) is common edible crab. It is widely distributed in the estuary and coastal waters of Korea, Japan, China, and Southeast Asia ( Meng et al., 2020 ). The only neuropeptides reported in this species include CHH ( Xie et al., 2014 ), MIH ( Wang et al., 2013 ), and CCAP ( Sun et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%